Nicotinic acid receptor agonists impair myocardial contractility by energy starvation. Issue 11 (21st September 2020) - Watson, William D.; Timm, Kerstin N.; Lewis, Andrew J.; Miller, Jack J. J.; Emmanuel, Yaso; Clarke, Kieran; Neubauer, Stefan; Tyler, Damian J.; Rider, Oliver J.
Abstract: Nicotinic acid receptor agonists have previously been shown to cause acute reductions in cardiac contractility. We sought to uncover the changes in cardiac metabolism underlying these alterations in function. In nine humans, we recorded cardiac energetics and function before and after a single oral dose of nicotinic acid using cardiac MRI to demonstrate contractile function and Phosphorus‐31 ( 31 P) magnetic resonance spectroscopy to demonstrate myocardial energetics. Nicotinic Acid 400 mg lowered ejection fraction by 4% (64 ± 8% to 60 ± 7%, P = .03), and was accompanied by a fall in phosphocreatine/ATP ratio by 0.4 (2.2 ± 0.4 to 1.8 ± 0.1, P = .04). In four groups of eight Wistar rats, we used pyruvate dehydrogenase (PDH) flux studies to demonstrate changes in carbohydrate metabolism induced by the nicotinic acid receptor agonist, Acipimox, using hyperpolarized Carbon‐13 ( 13 C) magnetic resonance spectroscopy. In rats which had been starved overnight, Acipimox caused a fall in ejection fraction by 7.8% (67.5 ± 8.9 to 60 ± 3.1, P = .03) and a nearly threefold rise in flux through PDH (from 0.182 ± 0.114 to 0.486 ± 0.139, P = .002), though this rise did not match pyruvate dehydrogenase flux observed in rats fed carbohydrate rich chow (0.726 ± 0.201). In fed rats, Acipimox decreased pyruvate dehydrogenase flux (to 0.512 ± 0.13, P = .04). Concentration of plasma insulin fell by two‐thirds in fed rats administered Acipimox (from 1695 ± 891 ng/L to 550 ± 222 ng/L, P = .005) in spite of glucose concentrations remaining the same. In conclusion, we demonstrate that nicotinic acid receptor agonists impair cardiac contractility associated with a decline in cardiac energetics and show that the mechanism is likely a combination of reduced fatty acid availability and a failure to upregulate carbohydrate metabolism, essentially starving the heart of fuel.